Principles of marketing - Kotler, Philip; Armstrong, Gary; Opresnik, Marc Oliver (Pearson Education Limited, 2021)
For principles of marketing courses that require a comprehensive text. Learn how to create value through customer connections and engagement. In a fast-changing, increasingly digital and social marketplace, it's more vital than ever for marketers to develop meaningful connections with their customers. Principles of Marketing helps students master today's key marketing challenge: to create vibrant, interactive communities of consumers who make products and brands an integral part of their daily lives. To help students understand how to create value and build customer relationships, Kotler and Armstrong present fundamental marketing information within an innovative customer-value framework. Thoroughly revised to reflect the major trends impacting contemporary marketing, the 18th Edition is packed with stories illustrating how companies use new digital technologies to maximize customer engagement and shape brand conversations, experiences, and communities.